Comparsion Between the Efficacy of Metformin Plus Clomiphene and Clomiphene Alone in the Treatment of Primary Infertility Due to Polycystic Ovarian Syndrome in Obese Women - Farkhanda Sadiq, Saira Ghafoor, Bibi Sara, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infertility is defined as the inability to conceive after one to two years of unprotected intercourse. It is of two types primary infertility and secondary infertility Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies affecting 5%–10% of reproductive age women. To compare the efficacy of metformin plus clomiphene and clomiphene alone in the treatment of primary infertility due to polycystic ovary syndrome in obese women Materials And Methods: It was Randomized Controlled Trial, which was conducted in the department of Obstetrics and Gynaecology, Hospital, Peshawar, between 30th May 2019 to 8th January 2022) Sample size will be 380 in each group using P 1 = 15%, P 2 = 22% and power of 80% and 95% confidence interval under WHO Software for sample size determination. Results: A total of 380 patients in each group were observed. Average age of the patients was 26.60 years+ 3.99SD with range of 19-35 years. Group A showed 88(23.2%) efficacies. Similarly Group B showed 68 (17.9%) efficacies. Efficacy was significant in both the groups with p-value=0.044. Conclusion: Metformin plus clomiphene is more efficacious than clomiphene alone in the treatment of primary infertility due to polycystic ovary syndrome in obese women. Keywords: Efficacy, metformin, clomiphene, polycystic ovary syndrome, primary infertility